Moving Advertisements Systematically Affect Gaze Behavior and Performance in the Soccer Penalty Kick - Paterson, Gareth; Kamp, John van der; Savelsbergh, Geert (Frontiers in Sports and Active Living, 2020)
The aim of the current study was to investigate whether a moving advertisement positioned behind the goal area would influence the visual attention of participants performing a soccer penalty kick, and, whether this would an effect on subsequent motor performance. It was hypothesized that if the (moving) advertisement would function as a distractor, then this would result in non-specific disruptions in penalty performance measures, especially affecting aiming location and precision. Alternatively, it was reasoned that, in line with the Dunker illusion, the moving advertisement would systematically affect perception of target location, resulting in changes in penalty performance and aiming that are specific for the direction of motion of the advertisement. To test these hypotheses, we investigated the gaze behavior and kicking performance of intermediate skilled soccer players taking penalty kicks in three differing advertisement conditions, namely no advertisement, a stationary advertisement, and a moving advertisement. The latter condition consisted of an advertisement moving from left to right and an advertisement moving from right to left. Results showed that a moving advertisement placed behind the goal area indeed caught the visual attention of soccer penalty kickers using a goalkeeper-dependent kicking strategy. Participants kicking performance tended to be less variable within the no advertisement condition compared to the moving advertisement condition. In addition, systematic, direction-specific effects on aiming were found when comparing conditions in which the advertisement moved in opposite directions. This pattern of findings indicate that the accuracy of the penalty kick is impacted by task-irrelevant contextual information.